« Parlez votre langue ! ». Injonctions plurilingues et violences symboliques faites aux élèves allophones - Maryse Adam Maillet (Recherches en didactique des langues et des cultures, 2021)
The injunction of school stakeholders to families has tended to shift from “speak French at home” to “speak your language at home”. This shift is not, in any way, progress to us. On the contrary, this injunction, by assigning an essentialist linguistic identity bears a highly symbolic violence, which is even more powerful and insidious than the traditional monolingual crusade. This is why calling on reflection (including reflexivity) is the only way to produce a relationship ethos truly respectful of otherness when training stakeholders and implementing policies in favor of a plurilingual and pluricultural education.